Making inflation visible: How incremental price increases become a public problem - Marcin Serafin; Marlena Rycombel; Marta Olcoń-Kubicka (economic sociology. perspectives and conversations, 2022)
The assumption that inflation is clearly visible to everyone can only be made in the case of hyperinflation or when inflation is high enough that prices are changing significantly from one month to the next across various markets. This direct relation between high inflation and individual experiences of changing prices was well described by Maurice Halbwachs in his posthumously published book The Collective Memory.
Keywords: 300